Best Answer

It depends on what you are solving for. If you are solving for 'y', then the answer would be:

y=4x+2

if you're solving for 'x':

x=1/4y-1

Q: What is the answer for 3y - 12x equals 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

12x - 9y = 6, 12x + 20y = 64 29y = 58 y = 2 x = 2

1: 12x - 9y = 6 2: 12x + 20y = 64 Subtract 1 from 2: 29y = 58 y = 2. So does x.

6(2x - 3y)

The y intercept is 7/3 and the slope is -4

2x-3y=5 and x-2y=12x-3y+2y=5 and x-2y+2y=12x-y=5 and x=12(1)-y=52-y=52-y-2=5-2-y=3y=-3(x,y) is (1,-3)

Related questions

8x-3y=6-4x gives 12x-3y=6 which in standard form is y=-2+4x

12x - 9y = 6, 12x + 20y = 64 29y = 58 y = 2 x = 2

3Y - 12X = 0add 12X to both sides3Y = 12Xdivide both sides integers by 3(3/3)Y = (12/3)XY = 4X---------------the function

1: 12x - 9y = 6 2: 12x + 20y = 64 Subtract 1 from 2: 29y = 58 y = 2. So does x.

x + 3y = 62x + y = -8Solve by substitution:x + 3y = 6 subtract 3y to both sidesx = 6 - 3y2x + y = -8 substitute 6 - 3y for x2(6 - 3y) + y = -812 - 6y + y = -812 - 5y = -8 subtract 12 to both sides-5y = -20 divide by -5 to both sidesy = 4x = 6 - 3yx = 6 - 3(4) = 6 - 12x = -6Thus, the solution of the system is (-6, 4).

6(2x - 3y)

12x-8y

The y intercept is 7/3 and the slope is -4

2x-3y=5 and x-2y=12x-3y+2y=5 and x-2y+2y=12x-y=5 and x=12(1)-y=52-y=52-y-2=5-2-y=3y=-3(x,y) is (1,-3)

6x-y=-14 2x-3y=6

The answer to -12x minus 17 equals negative 89 is x equals 6.

y = - 4x - 4